The Effects of Mandated Health Insurance Benefits for Autism on Out‐of‐Pocket Costs and Access to Treatment. (24th January 2015) - Chatterji, Pinka; Decker, Sandra L.; Markowitz, Sara
Abstract As of 2014, 37 states have passed mandates requiring many private health insurance policies to cover diagnostic and treatment services for autism spectrum disorders (ASDs). We explore whether ASD mandates are associated with out‐of‐pocket costs, financial burden, and cost or insurance‐related problems with access to treatment among privately insured children with special health care needs (CSHCNs). We use difference‐in‐difference and difference‐in‐difference‐in‐difference approaches, comparing pre–post mandate changes in outcomes among CSHCN who have ASD versus CSHCN other than ASD. Data come from the 2005 to 2006 and the 2009 to 2010 waves of the National Survey of CSHCN. Based on the model used, our findings show no statistically significant association between state ASD mandates and caregivers' reports about financial burden, access to care, and unmet need for services. However, we do find some evidence that ASD mandates may have beneficial effects in states in which greater percentages of privately insured individuals are subject to the mandates. We caution that we do not study the characteristics of ASD mandates in detail, and most ASD mandates have gone into effect very recently during our study period.